2005
DOI: 10.1111/j.1600-0463.2005.apm_10.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian ependymoma

Abstract: A 76-year-old woman presented with a large calcifying mass behind the bladder. The tumor contained solid areas of a yellowish white color. Microscopic examination revealed highly cellular solid areas with many typical ependymal perivascular pseudorosettes. The cells contained uniform round-to-oval nuclei, some of which had irregular contours, clumped chromatin and occasional prominent nucleoli. There was widespread geographic necrosis and there were 5 atypical mitotic figures per 10 high power fields. Glial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…It has been reported that, from the remnants left in the neural tube, ependymomas may develop in the sacrococcygeal extraspinal region, ovaries, paraovarian tissues, the omentum, the posterior mediastinum, and even in the lungs [18,31]. In the literature, there are very few ovarian ependymoma cases reported [11].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that, from the remnants left in the neural tube, ependymomas may develop in the sacrococcygeal extraspinal region, ovaries, paraovarian tissues, the omentum, the posterior mediastinum, and even in the lungs [18,31]. In the literature, there are very few ovarian ependymoma cases reported [11].…”
Section: Discussionmentioning
confidence: 98%
“…There is a hypothesis that extraventricular or cortical ependymomas may form from the insertion of an embryonic ependymal tissue remnant into the cerebral cortex during the brain parenchyma's development [7,30]. Within this, it has been reported that, although they generally form in the nervous system, they also very rarely form extracranially [11]. It is thought that extracranial ependymomas grow when the patient is carrying an embryo from remnants in the neural tube or multiply from teratomas [18,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports most patients with early stage received operation only [3,5,8] while patients with advanced stage administrated with adjuvan radiation and/or chemotherapy after cytoreductive surgery [1,3,6,7]. Patients with early stage have longer overall survival with less recurrence rates, so stage seems to be the most important prognostic parameter of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Ependymal rosettes can be similar to Call-Exner bodies of granulosa cell tumors [4][5][6]. Gland-like areas lined by cells with fibrillary cytoplasmic processes, perivascular pseudorosettes and positive satining for GFAP confirm the diagnosis of ovarian ependymoma [7,8]. Ependymomas can also stain positively for S-100, epithelial membrane antigen (EMA), neuron specific enolase (NSE), cytokeratin, CEA, vimentin, estrogen and progesterone receptors [9,10].…”
Section: Discussionmentioning
confidence: 99%